Influencia del programa socio bosque en la dinámica de los servicios ambientales de los bosques secos deciduos del Ecuador - Acosta Cevallos, Elena Gabriela (2015)
This paper analyzes the influence of “Programa Socio Bosque” in the dynamics of Environmental Services of Dry Deciduous Forests of Ecuador. These forests are formations under the warm plains of the Ecuadorian coast, have the characteristic of losing 75% of their leaves during the dry season. An area of 467.210,89 hectares of Dry Deciduous Forest, spread throughout the provinces of Manabí, Guayas, Santa Elena, El Oro and Loja are currently registered. Since 2008, the Ministry of Environment of Ecuador, implements a policy of incentives for the conservation of native forests, participants or partners in this program are committed to conservation areas in return receive an economic incentive per hectare conserved. Within the study, was identified a potential area of analysis corresponds to 372.492,77 hectares, these spaces were compared using a multitemporal study in three periods (1990-2000), (2001-2008) and (2009.2012), identifying changes in coverage vegetation and land use in the catchment area of dry deciduous forests. The results of multitemporal study show a change in the following classes: Native Forests have a trend of decreasing surface basically effects of deforestation. Agricultural Land greatly increases its surface by agricultural expansion. Increased surface Shrub and herbaceous vegetation, linked to natural regeneration of the potential analysis area. The Anthropogenic areas have considerable growth linked to urban sprawl. With these results the creation of a strategy Incentives, starting from a baseline allows the construction of a Policy Payment for Environmental Services in the country and for the benefit of citizens is proposed. These future strategies projected greater conservation area while maintaining the connectivity of ecosystems, biodiversity and adequate sustainable production.